Indonesia’s Archipelagic State Status: Current Development - Puspitawati, Dhiana (UI Scholars Hub, 2021)
A crucial, almost revolutionary, development in the international law of the sea was the recognition of archipelagic state principles within the United Nations Convention on the Law of the Sea 1982 (LOSC). The essential features of archipelagic state principle laid down by Part IV of LOSC include permission to draw straight archipelagic baselines around the outermost points of the outermost islands of archipelagos; and the recognition of the new and distinct legal regime of archipelagic water for the waters thus enclosed of a nature designed to accommodate the interests of maritime user states, that are states which carry out certain activities, including navigation, in the water areas falling under the jurisdiction of archipelagic states. Since this principle has been Indonesian national philosophical outlook even before the adoption of LOSC and provided within Article 25 (a) of the Indonesian Constitutions, it is submitted that all Indonesian national legislations related to ocean affairs should be based on the archipelagic state principles. This study looks at the legal application of archipelagic state principles in Indonesia within the framework of contemporary ocean governance principles. This paper argued that current development on Indonesian law of the sea as well as ocean governance shows less commitment to archipelagic state principles. Thus, it is submitted that archipelagic state principles should be re-stored as the basis of all ocean related legislations and governance.